5 Months Old Baby with Tension Pneumatocele - A Case Report (Chest & Heart Journal, 2023)
Pneumatoceles are thin walled air-filled pulmonary cysts which commonly develop as a complication of pneumonia. They are known to resolve spontaneously over several weeks or months. Rarely, they may result in complications of tension, infection, and rupture which may be life threatening and requires prompt attention.Tension pneumatocele enlarges significantly compressing adjacent lung and mediastinum resulting in cardiovascular collapse and may need definitive treatement. A case of 5 months old boy baby with tension peumatocele in right lower lobe underwent lobectomy has been described here.Chest Heart J. 2021; 45(1) : 47-52